2002
DOI: 10.1046/j.1365-8711.2002.05468.x
|View full text |Cite
|
Sign up to set email alerts
|

Orbital dynamics of three-dimensional bars - I. The backbone of three-dimensional bars. A fiducial case

Abstract: A B S T R A C TIn this series of papers we investigate the orbital structure of three-dimensional (3D) models representing barred galaxies. In the present introductory paper we use a fiducial case to describe all families of periodic orbits that may play a role in the morphology of threedimensional bars. We show that, in a 3D bar, the backbone of the orbital structure is not just the x1 family, as in two-dimensional (2D) models, but a tree of 2D and 3D families bifurcating from x1. Besides the main tree we hav… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
169
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 168 publications
(171 citation statements)
references
References 27 publications
2
169
0
Order By: Relevance
“…The ND is perpendicular to the main bar, which is horizontal 1 in Fig. 4 and is therefore most likely supported by the x2 family of bar orbits, which is elongated in this way (Skokos, Patsis & Athanassoula 2002). (The x3 orbits, which are also elongated perpendicular to the bar, are generally unstable (e.g.…”
Section: Global Properties Of the Modelmentioning
confidence: 87%
“…The ND is perpendicular to the main bar, which is horizontal 1 in Fig. 4 and is therefore most likely supported by the x2 family of bar orbits, which is elongated in this way (Skokos, Patsis & Athanassoula 2002). (The x3 orbits, which are also elongated perpendicular to the bar, are generally unstable (e.g.…”
Section: Global Properties Of the Modelmentioning
confidence: 87%
“…x y z W W W = 2:−2:−1" (these are also referred to as "x1v1" orbits by Skokos et al 2002a). Also seen is the 3: −2:0 resonance.…”
Section: Frequency Mapsmentioning
confidence: 94%
“…Indeed, studies of orbits in 2D N-body bars largely confirmed the picture arising from the study of periodic orbits and showed that many regular orbits elongated along the bar were parented by x1 orbits, a small fraction were parented by retrograde x4 orbits (Sparke & Sellwood 1987), and none were parented by prograde x2 orbits. The realization that bars can also undergo buckling instabilities (Combes & Sanders 1981;Raha et al 1991), which makes them develop substantial vertical thickness and peanut-shaped morphologies, led to the study of periodic orbits in three-dimensional bars (Pfenniger 1984;Martinet & de Zeeuw 1988;Pfenniger & Friedli 1991;Skokos et al 2002aSkokos et al , 2002b. It was shown that theappearance of specific morphological features in images of bars, such as the X-shape and peanut features seen in edge-on bars and the boxy/rectangular isophotes and "ansae" of face-on bars, could be explained by orbits trapped around specific periodic orbit families (Patsis et al 2002(Patsis et al , 2003(Patsis et al , 2010.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations